Peningkatan Daya Saing UMKM Pangan Melalui Inovasi Mesin Pemotong dan Pengukus di UKM Kerupuk Ikan Tambak Cemandi - Dhita Ayu Permata Sari; Hanna Zakiyya; Any Sutiadiningsih; Nugraha Prasetya Derajat (Universitas Negeri Surabaya, 2026)
Small fish cracker businesses still use manual methods to steam and cut dough, which makes them less productive, less consistent in quality, and less competitive. The goal of this community service project was to make and use semi-automatic equipment for steaming and cutting for UKM Kerupuk Ikan Payus Tambak Cemandi. The machine has a temperature-time control system for even steaming and an automatic slicer that keeps the thickness (1–2 mm) the same. Surveys, design, manufacture, functional testing, training, and monitoring were all parts of the process. The results reveal that production capacity went up from around 15 kg/day to about 30 kg/day, product quality got more consistent, and labor efficiency went up by 50%. Training in digital marketing and new packaging made the products even more competitive. This new idea shows how the right technology can help local small and medium-sized businesses (SMEs) improve productivity, ensure quality, and grow their markets.